2014
DOI: 10.1073/pnas.1316925111
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT1 signaling promotes HMGB1 hyperacetylation and nuclear translocation

Abstract: Extracellular high-mobility group box (HMGB)1 mediates inflammation during sterile and infectious injury and contributes importantly to disease pathogenesis. The first critical step in the release of HMGB1 from activated immune cells is mobilization from the nucleus to the cytoplasm, a process dependent upon hyperacetylation within two HMGB1 nuclear localization sequence (NLS) sites. The inflammasomes mediate the release of cytoplasmic HMGB1 in activated immune cells, but the mechanism of HMGB1 translocation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
275
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(286 citation statements)
references
References 42 publications
8
275
0
3
Order By: Relevance
“…Passive release, which occurs in the context of necrotic cell death, is nearly instantaneous. Active HMGB1 secretion is a much slower process that requires two essential steps: the initial step is to translocate nuclear HMGB1 to the cytoplasm, which depends on JAK-STAT signaling that will generate hyperacetylation of critical lysine residues located in the two NLS sites (26). This molecular modification of HMGB1 prevents the continuous bidirectional shuttle of HMGB1 between the cytoplasm and the nucleus and leads to cytoplasmic accumulation of hyperacetylated HMGB1.…”
Section: Extracellular Hmgb1 Releasementioning
confidence: 99%
“…Passive release, which occurs in the context of necrotic cell death, is nearly instantaneous. Active HMGB1 secretion is a much slower process that requires two essential steps: the initial step is to translocate nuclear HMGB1 to the cytoplasm, which depends on JAK-STAT signaling that will generate hyperacetylation of critical lysine residues located in the two NLS sites (26). This molecular modification of HMGB1 prevents the continuous bidirectional shuttle of HMGB1 between the cytoplasm and the nucleus and leads to cytoplasmic accumulation of hyperacetylated HMGB1.…”
Section: Extracellular Hmgb1 Releasementioning
confidence: 99%
“…Emerging evidence has revealed an important role for PKR (30) and STAT1 (28) in LPS-induced HMGB1 release. To evaluate this mechanism of SAA-mediated HMGB1 release, we examined the effects of TLR4/RAGE deficiency on SAAinduced activation of these signaling molecules.…”
Section: Requirement Of Tlr4/rage Receptors For Saa-induced Pkr Upregmentioning
confidence: 99%
“…The nucleus-to-cytoplasm translocation of HMGB1 is mediated by the STAT1-mediated acetylation of the HMGB1 nuclear-localization sequences (28). The extracellular HMGB1 release is regulated by caspase 1-and the doublestranded RNA-activated protein kinase R (PKR)-dependent inflammasome activation (29,30), pyroptosis (31) or necroptosis (32).…”
mentioning
confidence: 99%
“…HMGB1 is passively released by dying cells and actively generated in inflammatory conditions: it acts in the extracellular environment as a prototypical DAMP/alarmin. [10][11][12][13] Little is known on the role of HMGB1 in peritoneal carcinogenesis. We have recently observed that HMGB1 released as a consequence of 5-fluorouracil based chemotherapy activates autophagic and apoptotic pathways and might contribute to the resistance of cancer cells to conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%